Antagonism Between PEDF and TGF‐β Contributes to Type VI Osteogenesis Imperfecta Bone and Vascular Pathogenesis. (13th April 2022) - Kang, Heeseog; Aryal AC, Smriti; Barnes, Aileen M; Martin, Aline; David, Valentin; Crawford, Susan E; Marini, Joan C
ABSTRACT: Osteogenesis imperfecta (OI) is a heterogeneous genetic disorder of bone and connective tissue, also known as brittle bone disease. Null mutations in SERPINF1, which encodes pigment epithelium‐derived factor (PEDF), cause severe type VI OI, characterized by accumulation of unmineralized osteoid and a fish‐scale pattern of bone lamellae. Although the potent anti‐angiogenic activity of PEDF has been extensively studied, the disease mechanism of type VI OI is not well understood. Using Serpinf1 (−/−) mice and primary osteoblasts, we demonstrate that loss of PEDF delays osteoblast maturation as well as extracellular matrix (ECM) mineralization. Barium sulfate perfusion reveals significantly increased vessel density in the tibial periosteum of Serpinf1 (−/−) mouse compared with wild‐type littermates. The increased bone vascularization in Serpinf1 (−/−) mice correlated with increased number of CD31(+)/Endomucin(+) endothelial cells, which are involved in the coupling angiogenesis and osteogenesis. Global transcriptome analysis by RNA‐Seq of Serpinf1 (−/−) mouse osteoblasts reveals osteogenesis and angiogenesis as the biological processes most impacted by loss of PEDF. Intriguingly, TGF‐β signaling is activated in type VI OI cells, and Serpinf1 (−/−) osteoblasts are more sensitive to TGF‐β stimulation than wild‐type osteoblasts. TGF‐β stimulation and PEDF deficiency showed additive effects on transcription suppression of osteogenic markers and stimulation of pro‐angiogenic factors. Furthermore, PEDF attenuated TGF‐β‐induced expression of pro‐angiogenic factors. These data suggest that functional antagonism between PEDF and TGF‐β pathways controls osteogenesis and bone vascularization and is implicated in type VI OI pathogenesis. This antagonism may be exploited in developing therapeutics for type VI OI utilizing PEDF and TGF‐β antibody. © 2022 American Society for Bone and Mineral Research (ASBMR). This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA.